Quality and reliability of large-eddy simulations II - Salvetti, Maria Vittoria; Geurts, Bernard; Meyers, Johan; Sagaut, Pierre 1967- (Dordrecht, Netherlands Springer Dordrecht, 2011)
second Workshop on "Quality and Reliability of Large-Eddy Simulations", QLES2009, was held at the University of Pisa from September 9 to September 11, 2009. Its predecessor, QLES2007, was organized in 2007 in Leuven (Belgium). The focus of QLES2009 was on issues related to predicting, assessing and assuring the quality of LES. The main goal of QLES2009 was to enhance the knowledge on error sources and on their interaction in LES and to devise criteria for the prediction and optimization of simulation quality, by bringing together mathematicians, physicists and engineers and providing a platform specifically addressing these aspects for LES. Contributions were made by leading experts in the field. The present book contains the written contributions to QLES2009 and is divided into three parts, which reflect the main topics addressed at the workshop: (i) SGS modeling and discretization errors; (ii) Assessment and reduction of computational errors; (iii) Mathematical analysis and foundation for SGS modeling.
Part I SGS modeling and discretization errors: Error-landscape assessment of large-eddy simulations: a review, by Johan Meyers -- Numerical and physical instabilities in massively parallel LES of reacting Flows, by Thierry Poinsot -- Quality Issues of Combustion LES, by A M Kempf, M Pettit -- Energy cascade and spatial fluxes of filtered wall-turbulent flows, by A. Cimarelli, E. De Angelis -- A computational study of turbulent flow separation for a circular cylinder using skin friction boundary conditions, by Johan Hoffman, Niclas Jansson -- LES-SSAM for a high Reynolds number turbulent channel flow, by Remi Zamansky, Ivana Vinkovic, Mikhael Gorokhovski -- A new development of the dynamic procedure for the integral-based implicit filtering in large-eddy simulation, by Filippo M. Denaro, Giuliano De Stefano -- Reduced interaction between numerical and model errors through anisotropic filtering, by Marcello Meldi, Federico Perini -- Analysis of the subgrid models in the flow between rotating discs, by Artur Tyliszczak, Andrzej Boguslawski -- A priori analysis of an Isothermal, Turbulent Two-Phase Flow, by Alessandro Pecenko, J. G. M. Kuerten -- A Posteriori Analysis of Numerical Errors in Computing Scalar Variance, by Colleen M. Kaul, Venkat Raman, Guillaume Balarac, Heinz Pitsch -- Quality of classical and variational multiscale LES simulations of the flow around a circular cylinder, by Hilde Ouvrard, Maria Vittoria Salvetti, Bruno Koobus, Alain Dervieux -- LES model intercomparisons for the stable atmospheric boundary layer, by Arnold F. Moene, Peter Baas, Fred C. Bosveld, Sukanta Basu -- Evaluating Subgrid-Scale Models for Large-Eddy Simulation of Turbulent Katabatic Flow, by Bryan A. Burkholder, Evgeni Fedorovich, Alan Shapiro -- Large-eddy simulation of pyroclastic density currents, by Tomaso Esposti Ongaro, Sara Barsotti, Augusto Neri, Maria Vittoria Salvetti -- Analysis of SGS effects on dispersed particles in LES of heated channel Flow, by Jacek Pozorski and Miros?aw ?uniewski -- Relevance of approximate deconvolution for one-way coupled motion of inertial particles in LES of turbulent channel flow, by Marek Jaszczur, Bernard J. Geurts,, J.G.M. Kuerten -- Inertial particle segregation and deposition in large-eddy simulation of turbulent wall-bounded flows, by Cristian Marchioli, Maria Vittoria Salvetti, Alfredo Soldati -- Scalar sub-grid energy in large-eddy simulation of turbulent flames: mesh quality criterion, by Luc Vervisch, Pascale Domingo, Guido Lodato, Denis Veynante -- Accuracy, Reliability and Performance of Spray Combustion Models in LES, by Srikant Srinivasan, Andrew G. Smith, Suresh Menon -- LES of Triangular-stabilized Lean Premixed Turbulent Flames with an algebraic reaction closure: Quality and Error Assessment, by B. Manickam, J. Franke, S. P. R. Muppala, F. Dinkelacker -- Grid Effects on LES Thermo-Acoustic Limit-Cycle of a Full Annular Aeronautical Engine, by Pierre Wolf, Laurent Y.M. Gicquel, Gabriel Staffelbach, Thierry Poinsot -- Extension of LES approaches to conductive fluids and plasmas, by P. Morel, D. Carati, F. Merz, T. Görler, F. Jenko -- Part II Assessment and reduction of computational errors: Grid Design and the Fate of Eddies in External Flows, by Philippe R. Spalart, Mikhail Kh. Strelets, and Andrey Garbaruk -- How to estimate the resolution of an LES of recirculating flow, by Lars Davidson -- Quality assessment of Dynamic Finite Difference schemes on the Taylor-Green Vortex, by Dieter Fauconnier, Chris De Langhe, Erik Dick -- Stochastic Coherent Adaptive Large-Eddy Simulation with explicit Filtering, by Giuliano De Stefano, Oleg V. Vasilyev -- Error reduction in LES via adaptive moving grids, by Claudia Hertel, Jochen Fröhlich -- Influence of Reynolds number and grid resolution on large-eddy simulations of self-similar jets based on relaxation filtering, by Christophe Bogey, Christophe Bailly -- An Examination of the Spatial Resolution Requirements for LES of a Compressible Jet, by James R. DeBonis -- A Computational Uncertainty Analysis of LES/DNS: towards building a reliable engineering turbulence prediction capability, by Hongyi Xu -- Computational error-minimization for LES of non-premixed turbulent Combustion, by Bernard J. Geurts, Andreas Kempf -- Assessment of eddy resolving techniques for the flow over periodically arranged hills up to Re=37,000, by Michael Manhart, Christoph Rapp, Nikolaus Peller, Michael Breuer, Orhan Aybay, Jordan A. Denev, Carlos J. Falconi -- Part III Mathematical analysis and foundation for SGS modeling From suitable weak solutions to entropy viscosity, by Jean-Luc Guermond, Richard Pasquetti, Bojan Popov -- A new deconvolution approach, by Massimo Germano -- Horizontal Approximate Deconvolution for Stratified Flows: Analysis and Computations, by Luigi C. Berselli, Traian Iliescu, Tamay Özgökmen -- The effect of subfilter-scale physics on regularization models, by Jonathan Pietarila Graham, Darryl Holm, Pablo Mininni, Annick Pouquet -- When does eddy viscosity damp subfilter scales sufficiently?, by Roel Verstapp
Electronic reproduction.
Keywords: Eddies -- Simulation methods -- Reliability -- Congresses; Eddies -- Mathematical models -- Congresses